Cambios cognoscitivos en la enfermedad mental de pacientes que asisten al Programa de Hospital Día del Hospital Psiquiátrico Universitario del Valle (2008)
Research has shown that mental illness is caused by cognitive dysfunctions expressed in disorder of ideas and feelings with profound alterations for reasoning, behavioural disorders, and difficulties to recognize reality and adapt to the normal life challenges. The goal of this study was to describe by neuropsychological evaluation the cognitive changes in a group of patients with mental illness who attended a Day Hospital program, a therapeutic space designed for the rehabilitation, care and support of the patients: 25 patients between 16 and 61 years old with a minimum escolarity of five years were randomly selected. A neuropsychological evaluation was conducted before the treatment (pre-evaluation) and five months after the beginning of treatment (post-evaluation). The Brief Neuropsychological Evaluation in Spanish-Neuropsi (Ostrosky, Ardila and Roselli, 1994) was applied. The pre-evaluation results showed that the patients with mental illness present cognitive changes in attention, immediate memory, semantic key evocation, evocation by recognition, visual memory, verbal understanding and semantic verbal fluidity, visoconstructional skills, conceptual, and motor executive functions; however, these cognitive functions improve when patients regularly attend to the Day Hospital program. These results highlight the importance of the interdisciplinary therapeutic work, in addition to pharmacotherapy, in order to achieve more stable cognitive changes. Key words: cognitive changes, psychiatric patients, rehabilitation, Day Hospital.